Hexahelixs collaboration in the development of traditional village ecotourism based on animal welfare from the perspective of tri hita karana - Parwati, Ni Kadek Desi; Subanda, I Nyoman (Jurnal Konseling dan Pendidikan, 2025)
Traditional village ecotourism development based on animal welfare requires a comprehensive and collaborative approach to ensure sustainability. This study examines the role of Hexahelix collaboration, integrating government, businesses, academia, media, communities, and financial institutions, in promoting sustainable tourism within the framework of Tri Hita Karana philosophy. The research aims to explore how this collaborative model enhances economic benefits, environmental conservation, and cultural preservation while ensuring ethical treatment of animals. This study employs a mixed-methods approach, combining qualitative and quantitative techniques. Qualitative data were collected through interviews, observations, and document analysis, while quantitative data were gathered through surveys and statistical analysis. Thematic analysis is used to assess stakeholder interactions, policy impacts, and community engagement. Data validation is ensured through triangulation methods to enhance the reliability of findings. The results indicate that active community participation, supported by governmental policies and private sector engagement through Corporate Social Responsibility (CSR), significantly contributes to the success of animal-friendly tourism. Ritual practices like Tumpek Kandang reinforce ethical animal treatment, while media involvement enhances public awareness of sustainable tourism practices. However, challenges such as coordination among stakeholders and resource limitations remain barriers to full implementation. Despite its effectiveness, the Hexahelix model requires continuous refinement to address long-term ecological and economic resilience issues. This study suggests that future research should focus on evaluating long-term impacts and refining policies to optimize the balance between tourism development and conservation efforts. The findings provide practical insights for policymakers, businesses, and communities in adopting sustainable tourism models based on local wisdom and ethical treatment of animals